2022
DOI: 10.1530/jme-22-0012
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine and molecular factors of increased female reproductive performance in the Dummerstorf high-fertility mouse line FL1

Abstract: The Dummerstorf high-fertility mouse line FL1 is a worldwide unique selection experiment for increased female reproductive performance. After more than 190 generations of selection these mice doubled the amount of offspring per litter compared to the unselected control line. FL1 females have a superior lifetime fecundity and the highest Silver fecundity index that has been described in mice, while their offspring show no signs of growth retardation. The reasons for the increased reproductive performance remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(11 citation statements)
references
References 60 publications
(61 reference statements)
1
10
0
Order By: Relevance
“…The authors concluded that the expression of Sgk1 in GCs is induced by FSH via activators of the PKA pathway [ 31 ]. However, like previously described, FSH is significantly decreased in FL1 mice compared to ctrl mice [ 21 ]. However, FSH is not the only hormone that has the ability to regulate Sgk1 expression.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…The authors concluded that the expression of Sgk1 in GCs is induced by FSH via activators of the PKA pathway [ 31 ]. However, like previously described, FSH is significantly decreased in FL1 mice compared to ctrl mice [ 21 ]. However, FSH is not the only hormone that has the ability to regulate Sgk1 expression.…”
Section: Discussionsupporting
confidence: 79%
“…During follicular development, Timp1 expression can be regulated directly by the PKA signaling pathway or indirectly through IGF1 [ 26 ]. Strikingly, FSH levels are significantly decreased in FL1 mice [ 21 ] and also IGF1 levels are significantly lower in FL1 mice in estrus. The transcriptome analysis revealed no evidence that the receptors of FSH or IGF1 are differentially regulated in FL1 mice.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations